Pojęcia zdarzenia w obowiązkowych ubezpieczeniach odpowiedzialności cywilnej zawodowej - Wieteska, Stanisław (Event Conception in Obligatory Professional Civilian Insurance Responsibility, 2008)
The paper presents problems of responsibility in non life insurance. There is one very importance problem, which concerns professional civilian. This paper presents the relation between the man and events. It also says about the events classification and hazards of events. At the end of the paper we try to create the definition of the event conception in professional responsible civilian insurance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 474-483